Detection of Zymoseptoria tritici SDHI‐insensitive field isolates carrying the SdhC‐H152R and SdhD‐R47W substitutions. Issue 12 (8th April 2016) - Dooley, Hilda; Shaw, Michael W; Mehenni‐Ciz, Jeanne; Spink, John; Kildea, Steven
Abstract: BACKGROUND: Succinate dehydrogenase inhibitor (SDHI) fungicides are important in the management of Zymoseptoria tritici in wheat. New active ingredients from this group of fungicides have been introduced recently and are widely used. Because the fungicides act at a single enzyme site, resistance development in Z. tritici is classified as medium‐to‐high risk. RESULTS: Isolates from Irish experimental plots in 2015 were tested against the SDHI penthiopyrad during routine monitoring. The median of the population was approximately 2 times less sensitive than the median of the baseline population. Two of the 93 isolates were much less sensitive to penthiopyrad than the least sensitive of the baseline isolates. These isolates were also insensitive to most commercially available SDHIs. Analysis of the succinate dehydrogenase coding genes confirmed the presence of the substitutions SdhC ‐H152R and SdhD ‐R47W in the very insensitive isolates. CONCLUSION: This is the first report showing that the SdhC ‐H152R mutation detected in laboratory mutagenesis studies also exists in the field. The function and relevance of this mutation, combined with SdhD ‐R47W, still needs to be determined. © 2016 Society of Chemical Industry